Evaluation of dentinal tubule penetration depth and push-out bond strength of AH 26, BioRoot RCS, and MTA Plus root canal sealers in presence or absence of smear layer - Sevinç Aktemur Türker; Emel Uzunoğlu; Nuhan Purali (Tabriz University of Medical Sciences, 2018)
Background.This study compared the effect of smear layer on the penetration depth and push-out bond strength of various root canal sealers. Methods.A total of 90 extracted human mandibular premolars were assigned into 2 groups: smear layer preserved and smear layer removed. Then the roots were further divided into 3 subgroups according to the sealer tested: AH 26, BioRoot RCS and MTA Plus. Obturation was performed with gutta-percha and the relevant sealer was mixed with 0.1% rhodamine B. Three 1-mm-thick slices were obtained from the mid-third area of each root. Two slices were selected for the push-out test and the remaining slice was used to calculate the dentinal tubule penetration depth and percentage. Results.The retention of MTA Plus and BioRoot RCS was higher than that of AH 26 when the smear layer was preserved (P<0.05). BioRoot RCS showed the lowest penetration depth when the smear layer was removed (P<0.05). Conclusion.Dentinal tubule penetration of root canal sealers had a limited effect on their adhesion to root canal wall.